1980
DOI: 10.1002/jclp.6120360218
|View full text |Cite
|
Sign up to set email alerts
|

Training parents as therapists: A comparison between individual parent‐child interaction training and parent group didactic training

Abstract: Children with home behavior problems frequently are treated via training their parents to become behavior therapists for their own children. One well‐established approach has been to use didactic group training. Another approach involves parent training in specific parent‐child interaction patterns through the use of modeling, in vivo practice, and immediate feedback. In this study, the effectiveness of these two methods was compared via multiple outcome measures, which included both direct therapist observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(60 citation statements)
references
References 8 publications
0
59
0
1
Order By: Relevance
“…Reported reliability coefficients (Cronbach's alpha) have ranged from .88 to .91, with good stability over a 4-month period (.85) (Brestan et al 1999;Eisenstadt et al 1993;Eyberg and Matarazzo 1980). Low to moderate correlations (.36-.49) were reported between the TAI scores and changes during treatment.…”
Section: Modified Therapy Attitude Inventorymentioning
confidence: 84%
See 1 more Smart Citation
“…Reported reliability coefficients (Cronbach's alpha) have ranged from .88 to .91, with good stability over a 4-month period (.85) (Brestan et al 1999;Eisenstadt et al 1993;Eyberg and Matarazzo 1980). Low to moderate correlations (.36-.49) were reported between the TAI scores and changes during treatment.…”
Section: Modified Therapy Attitude Inventorymentioning
confidence: 84%
“…Reliability ratings for parent behaviors range from .67 to 1.0, with a mean of .91 (Aragona and Eyberg 1981;Matarazzo 1980: Robinson and. The DPICS has distinguished between pre-and post-treatment data (Eisenstadt et al 1993;McNeil et al 1991), different treatments (Eyberg and Matarazzo 1980), and interaction patterns among diverse family populations (Aragona and Eyberg 1981). …”
Section: Skill Acquisitionmentioning
confidence: 99%
“…The mean inter-rater reliability for parental behavior for the original DPICS was .91. Several studies have also found the DPICS to be sensitive to treatment effects (e.g., Eyberg & Matarazzo, 1980;Webster-Stratton, Hollinsworth, & Kolpacoff, 1989). In the present study, a total of 50 live inter-observer observations were conducted over the course of the study.…”
mentioning
confidence: 97%
“…Hay muchos estudios sobre su efectividad y efi cacia, en los que se han demostrado mejoras clínicas y estadísticamente signifi cativas con niños con conductas problema, así como la generalización de los resultados en la casa (Hembree-Kigin y McNeil, 1995;Herschell, Calzada, Eyberg, y McNeil, 2002), frente a listas de espera o grupos de control (Bagner y Eyberg, 2007;Chaffi n, Silovsky, Funderburk, Valle, Brestan, Balachova, Jackson, Lensgraf, y Bonner, 2004;Eyberg y Matarazzo, 1980;McNeil, Capage, Bahl y Blanc, del DSM-IV (APA, 1994) del trastorno negativista desafi ante (F91.3). Es decir, un comportamiento negativista y desafi ante (pataletas o rabietas, discusiones y desafíos a los adultos, no cumplir las demandas de éstos, etc.)…”
unclassified